The willingness of parents to vaccinate their children younger than 12 years against COVID-19: a cross-sectional study in Malaysia - Ng, Diana Leh-Ching; Gan, Gin Gin; Chai, Chee Shee; Nur Adila, Anuar; Woweham, Sindeh; Chua, Wei‑Jing; Asri, Said; Tan, Seng‑Beng (Springer Nature, 2022)
Background: The initiation of a new drug, for instance, the coronavirus disease 2019 (COVID‑19) vaccine in children could be a source of major concern for parents. This study aims to determine the willingness of parents in Malaysia to vaccinate their children younger than 12 years against COVID‑19.